2015
DOI: 10.1371/journal.pone.0124443
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Leymus chinensis Individual Aboveground Biomass Decline in Natural Semiarid Grassland Induced by Overgrazing: A Study at the Plant Functional Trait Scale

Abstract: Natural grassland productivity, which is based on an individual plant’s aboveground biomass (AB) and its interaction with herbivores, can obviously affect terrestrial ecosystem services and the grassland’s agricultural production. As plant traits have been linked to both AB and ecosystem success, they may provide a useful approach to understand the changes in individual plants and grassland productivity in response to grazing on a generic level. Unfortunately, the current lack of studies on how plant traits af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 45 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…Depending on the model and variable, it was necessary to alter the relationship between a measured L. chinensis functional trait and the rest of the model. We compared the utility of each functional trait index within the SEM based on a number of measures, including the power of the particular model for explaining the variation in L. chinensis biomass accumulation (R 2 ), measures of model significance and fit (χ 2 ), and the significance of the functional trait variables within the model (significance of regression weights) (Li et al, 2015b). SEM analysis was performed using IBM SPSS AMOS 18.0 software packages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the model and variable, it was necessary to alter the relationship between a measured L. chinensis functional trait and the rest of the model. We compared the utility of each functional trait index within the SEM based on a number of measures, including the power of the particular model for explaining the variation in L. chinensis biomass accumulation (R 2 ), measures of model significance and fit (χ 2 ), and the significance of the functional trait variables within the model (significance of regression weights) (Li et al, 2015b). SEM analysis was performed using IBM SPSS AMOS 18.0 software packages.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all grassland plant species have the same phenotypic plasticity reaction (Díaz et al, 2007). For example, distinctions could be made between "mowing-susceptible" and "mowing-resistant" plants in their responses to long-term stresses in heterogeneous habitats, and L. chinensis is the dominant species in Inner Mongolian grassland that is mowing-susceptible (Li et al, 2015b). Therefore, the reduction in physical characteristics of L. chinensis will likely have a substantial effect on the structure and functioning of grassland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of experimental evidence suggests that grassland plants show rapid phenotypic plasticity when exposed to such biotic and abiotic stresses (Li et al, 2015a). For example, Couso and Fernandez (2012) reported that the most tolerant species had the highest morphological plasticity in an underlying trait in three Patagonian steppe grasses.…”
Section: Introductionmentioning
confidence: 99%
“…Some human-induced factors, including overpopulation, overgrazing from livestock, and transportation, were also identified as being threatening factors for the grassland ecosystem [23][24][25][26]. Intensified human disturbance due to increased accessibility to remote regions, as a result of the construction of more road networks, have led to vegetation degradation in many parts of the world [17,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%